2012
DOI: 10.1111/j.1445-2197.2012.06248.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of handover on the outcomes of small bowel obstruction in an acute care surgery model

Abstract: Background: An acute care surgery (ACS) model was introduced to manage emergency surgical presentations efficiently. The aim of this study was to evaluate the impact of patient handover in an ACS model on the outcomes of adhesive small bowel obstruction (SBO). Methods: A retrospective study was performed on patients who were admitted with adhesive SBO at Prince of Wales Hospital. The cohort consisted of all patients treated by the ACS team from its introduction in September 2005 to February 2011. Patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 37 publications
1
28
1
Order By: Relevance
“…In an Australian survey, 65% (total of 88 surgeons) of surgeons who responded were satisfied with the handover they received from their colleagues. Handing over patients did not affect patient outcome in the ASU model of care . For small bowel obstruction cases, delaying surgery until the next day and handing over of patients with unresolved uncomplicated small bowel obstruction were shown to decrease after‐hours operating, without an increase risk in need for small bowel resection or complication rates …”
Section: Review Of Gsa 12‐point Planmentioning
confidence: 95%
See 1 more Smart Citation
“…In an Australian survey, 65% (total of 88 surgeons) of surgeons who responded were satisfied with the handover they received from their colleagues. Handing over patients did not affect patient outcome in the ASU model of care . For small bowel obstruction cases, delaying surgery until the next day and handing over of patients with unresolved uncomplicated small bowel obstruction were shown to decrease after‐hours operating, without an increase risk in need for small bowel resection or complication rates …”
Section: Review Of Gsa 12‐point Planmentioning
confidence: 95%
“…53,54 For small bowel obstruction cases, delaying surgery until the next day and handing over of patients with unresolved uncomplicated small bowel obstruction were shown to decrease after-hours operating, without an increase risk in need for small bowel resection or complication rates. 54 With the evolution of electronic medical records, handovers can be done with greater efficiency as clinical notes, pathology results and medical imaging are all available within a single portal. The timing and information which is handed over to the new surgeon can be documented so that there will be no confusion.…”
Section: Egs Should Be Consultant Ledmentioning
confidence: 99%
“…To our knowledge, three studies have assessed the impact of the ASU model on the management and outcomes of SBO . Lien et al .…”
Section: Discussionmentioning
confidence: 71%
“…Demonstrated benefits included reduced time to theatre and overall hospital stay, decreased after‐hours operation, use of preoperative computed tomography (CT) imaging and post‐operative complications . To our knowledge, only three small studies have analysed the impact of the ASU on the management and outcomes of SBO . Recent meta‐analysis has found that the data regarding the management of SBO is insufficient …”
Section: Introductionmentioning
confidence: 99%
“…This new model of care was presumed to improve outcomes compared to the traditional method of covering EGS with an on call general surgeon (4, 5, 6). Since ACS was first conceptualized as a novel model of care, several single-center retrospective studies have shown improved outcomes after implementation of ACS for a number of non-trauma surgical emergencies including appendicitis (7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17). …”
Section: Introductionmentioning
confidence: 99%